## 130 Reputation

6 years, 153 days

## How to find sgn on maple?...

Maple 18

How to find sgn on maple?

signum.mw

## How to integrate the expression when x i...

Maple 18

How to evaluate the integration when ?

integration_24sep.mw

## How to simplify this?...

Maple 18

xE.mw

I integrate the expression maple but the result is large. How to furtherxE.mw reduce the size of the result? Also, what is dilog on maple?

## How to calculate this?...

Maple 18

, where  is a complex parameter,  is a real constant and, , then how to calculate |u|^{2} on maple?

## Why Maple is not plotting the solution?...

Maple 18

 > restart;
 > with(PDEtools):
 > with(plot):
 > A1:=Matrix([[phi,(chi),conjugate(phi),conjugate(chi)],           [chi,(phi),conjugate(chi),conjugate(phi)],           [lambda*phi,-(lambda)*(chi),            conjugate(lambda)*conjugate(phi),-conjugate(lambda)*conjugate(chi)],           [lambda*chi,-(lambda)*(phi),            conjugate(lambda)*conjugate(chi),-conjugate(lambda)*conjugate(phi)]]);
 (1)
 > d1 := LinearAlgebra:-Determinant(A1):
 > d1; length(%);
 (2)
 > den:=simplify(d1,size); length(%);
 (3)
 >
 > con1:=phi=exp(I*lambda*(x-t/(4*lambda^2)-w^2)):con2:=chi=exp(-I*lambda*(x-t/(4*lambda^2)-w^2)):
 >
 > den1:=simplify(dsubs({con1,con2},den));
 (4)
 > plot3d(subs(Re(lambda)=1, Im(lambda)=.2, w=1, rhs(den1)),x=-6..6, t=-6..6)
 >
 >